2012
DOI: 10.1107/s1744309112038675
|View full text |Cite
|
Sign up to set email alerts
|

Purification, crystallization and preliminary X-ray crystallographic analysis of the ETS domain of human Ergp55 in complex with thecfospromoter DNA sequence

Abstract: The Ergp55 protein belongs to the Ets family of transciption factors. The Ets transcription factors are involved in various developmental processes and the regulation of cancer metabolism. They contain a highly similar DNA-binding domain known as the ETS domain and have diverse functions in oncogenesis and physiology. The Ets transcription factors differ in their DNA-binding preference at the ETS site and the mechanisms by which they target genes are not clearly understood. To understand its DNA-binding mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…ETS1 is known to regulate genes involved in both T-and NK-cell differentiation and activation (40)(41)(42). Further, members of the ETS1 transcription factor family bind to the promoters of effector T cell-relevant genes such as perforin and cfos to regulate their expression (43)(44)(45), so we next considered whether ETS1 might bind to the promoter of NKG7. Using CHIP-qPCR, we confirmed that ETS1 was indeed associated with the NKG7 promoter in CD8 + T cells isolated from healthy human donors (Fig.…”
Section: The Transcription Factor Ets1 Is a Negative Regulator Of Nkg7 Expressionmentioning
confidence: 99%
“…ETS1 is known to regulate genes involved in both T-and NK-cell differentiation and activation (40)(41)(42). Further, members of the ETS1 transcription factor family bind to the promoters of effector T cell-relevant genes such as perforin and cfos to regulate their expression (43)(44)(45), so we next considered whether ETS1 might bind to the promoter of NKG7. Using CHIP-qPCR, we confirmed that ETS1 was indeed associated with the NKG7 promoter in CD8 + T cells isolated from healthy human donors (Fig.…”
Section: The Transcription Factor Ets1 Is a Negative Regulator Of Nkg7 Expressionmentioning
confidence: 99%